Składniki mineralne w orzechach występujących w składzie „mieszanek studenckich” = Minerals in nuts which are components of „Trail Mix” - Mikołajczak, Natalia (Journal of Education, Health and Sport, 2016)
Mikołajczak Natalia. Składniki mineralne w orzechach występujących w składzie „mieszanek studenckich” = Minerals in nuts which are components of „Trail Mix”. Journal of Education, Health and Sport. 2016;6(9):832-840. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159445 http://ojs.ukw.edu.pl/index.php/johs/article/view/3919 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. SKŁADNIKI MINERALNE W ORZECHACH WYSTĘPUJĄCYCH W SKŁADZIE „MIESZANEK STUDENCKICH” Minerals in nuts which are components of „Trail Mix” Natalia Mikołajczak Katedra Przetwórstwa i Chemii Surowców Roślinnych Wydział Nauki o Żywności, Uniwersytet Warmińsko-Mazurski w Olsztynie Uniwersytet Warmińsko-Mazurski w Olsztynie, Katedra Przetwórstwa i Chemii Surowców Roślinnych Pl. Cieszyński 1, 10-726 Olsztyn e-mail: natalia.mikolajczak@uwm.edu.pl Streszczenie Wprowadzenie i cel pracy: Orzechy stanowią cenną grupę żywności pod względem wartości żywieniowej, dlatego też są jednym z głównych składników wykorzystywanych w produkcji mieszanek studenckich. Obecność orzechów w codziennej diecie konsumenta ma pozytywny wpływ na organizm poprzez redukcję poziomu cholesterolu we krwi, przeciwdziałanie nowotworom i cukrzycy czy również wspomaganie utraty masy ciała. Wszystkie te korzyści wynikają ze składu chemicznego orzechów i obecności w nich wielu wartościowych składników odżywczych, w szczególności składników mineralnych. Celem pracy był przegląd aktualnego piśmiennictwa na temat zawartości poszczególnych składników mineralnych w orzechach, będących składnikami tradycyjnych mieszanek studenckich, czyli laskowych, włoskich, arachidowych, nerkowcach oraz migdałach. Skrócony opis stanu wiedzy: Orzechy to cenne źródło składników mineralnych, zarówno mikro, jak i makroelementów. Przede wszystkim, orzechy laskowe, włoskie, arachidowe oraz migdały dostarczają znacznych ilości potasu, którego zawartość w 100 g surowca odnotowuje się na poziomie wyższym niż 500 mg. Z kolei zawartość fosforu obecna jest na zbliżonym poziomie jedynie w migdałach. Mikroelementy takie jak żelazo, miedź, cynk i mangan występują we wszystkich orzechach w ilości 5-10 mg/100 g. Podsumowanie: Zebrane dane literaturowe potwierdzają fakt, że analizowane rodzaje orzechów są cennym źródłem zarówno mikro, jak i makroelementów. Są one bogactwem potasu, fosforu, magnezu oraz wapnia. Ponadto, dostarczają także znacznych ilości żelaza, cynku oraz manganu. Słowa kluczowe: składniki mineralne, orzechy laskowe, orzechy włoskie, orzechy arachidowe, migdały Abstract Introduction and aim: Nuts are a valuable food group in terms of nutritional value, also they are one of the main ingredients used in the manufacture of mixtures student. The presence of these fruits in the daily diet of the consumer has a positive effect on the body by reducing level of the cholesterol in blood, counteracting the cancer and diabetes or supporting weight loss. All of these benefits are the result of chemical composition of nuts and the presence of many valuable nutrients, especially mineral elements. The aim of this article is to review the current literature on the participation of the individual minerals in nuts, which are components of the traditional mixtures student: hazelnuts, walnuts, peanuts, cashews and almonds. Brief description of the state of knowledge: Nuts are a valuable source of minerals, both micro and macroelements. Hazelnuts, walnuts, peanuts and almonds provide large amounts of potassium, the content in 100 g of raw material recorded at a level higher than 500 mg. In turn, the content of phosphorus is present at a similar level only in almonds. Trace elements such as iron, copper, zinc and manganese are present in all nuts in an amount of 5-10 mg/100 g. Summary: The data collected from the literature confirm that the analyzed kinds of nuts are a valuable source of both micro and macroelements. They are richness of potassium, phosphorus, magnesium and calcium. In addition, they also provide large amounts of iron, zinc and manganese. Key words: minerals, hazelnuts, walnuts, peanuts, almonds